Cystic Fibrosis: A Pocket Guide. (1st October 2020) - Roughley, Mark; MacDougall, Lawrie; Erolin, Caroline
Abstract: In 2010, an iPad app titled ' A Patient ' s Guide to Cystic Fibrosis ' was developed for use by Cystic Fibrosis (CF) clinical nurse specialists during a patient's annual review. Feedback from pseudo-CF patients and NHS staff including CF clinical nurse specialists and respiratory consultants about the appearance, usability and content of the app and iPad interface, and the appropriateness of the app for CF patients was positive. The visual images, animations and interactive elements of the app were sufficient in providing an engaging experience for the user. The app was deemed suitable for patients and set a foundation for the development of comprehensive and interactive CF patient information learning tools. Since 2010, the prevalence and popularity of iPad apps in healthcare have soared and apps now have the capability to include more interactive touch-based experiences with digital content such as 3D models. The original iPad app was re-developed as an Apple iBook and an Android app titled ' Cystic Fibrosis: A Pocket Guide '. This paper describes the design, development and feedback on the original iPad app and its subsequent variants, and concludes with reflections from the specialist CF nurses, who have continued to use pocket guide over 10 years.